2009
DOI: 10.1007/s10490-009-9135-6
|View full text |Cite
|
Sign up to set email alerts
|

Internal governance mechanisms and firm performance in China

Abstract: Internal governance mechanisms, Ownership concentration, Controlling shareholder, Board of directors, Supervisory board,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
153
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(182 citation statements)
references
References 54 publications
(73 reference statements)
8
153
2
4
Order By: Relevance
“…The results imply that adding more directors to the board will decrease the financial performance of the firm, suggesting that a large board may not necessarily increase the value to the company. This is supported by previous studies by [27,29,49,51]. Boubaker et al found that large boards result in a loss of productivity and losses are mainly due to increased difficulties in coordinating the efforts of multiple individuals, which also results in slower decision-making and more free riding [52].…”
Section: Random Effects Model: Board Size and Firm Performance (Roe)supporting
confidence: 67%
“…The results imply that adding more directors to the board will decrease the financial performance of the firm, suggesting that a large board may not necessarily increase the value to the company. This is supported by previous studies by [27,29,49,51]. Boubaker et al found that large boards result in a loss of productivity and losses are mainly due to increased difficulties in coordinating the efforts of multiple individuals, which also results in slower decision-making and more free riding [52].…”
Section: Random Effects Model: Board Size and Firm Performance (Roe)supporting
confidence: 67%
“…The listed firms in China showed a correlation between corporate governance and the firms' performance, where the estimated coefficient values are 0.3057 and 0.4575 for Tobin's Q model and ROA model, respectively. This is consistent with the previous results of Hu et al (2010), Sami et al (2011), Estrin andPrevezer (2011), and Masulis et al (2012). Lastly, there is also a positive and significant contribution by corporate governance to firm performance in Indonesia.…”
Section: The Role Of Corporate Governancesupporting
confidence: 92%
“…Similar to the perceptions about the boards of directors, most people perceive the supervisory boards to be ineffective in corporate governance because of the strong influence of controlling shareholders (Dahya, Karbhari, Xiao, & Yang, 2003;Shan, 2013;Xiao et al, 2004). Empirical evidence is consistent with this perception, showing that supervisory boards are not significantly associated with executive compensation Conyon & He, 2012), firm performance (Buck et al, 2008;Gang, 2007;Hu et al, 2010), expropriation (Shan, 2013), or firm decisions such as auditor switching and corporate social responsibility (Jia & Zhang, 2011;Lin & Liu, 2009). Thus, like the boards of directors, the supervisory boards have not yet become an effective internal corporate governance mechanism.…”
Section: Internal Mechanism: Boards Of Directorsmentioning
confidence: 87%